Contamination of raw milk with Bacillus cereus from farm to retail in Abidjan, Côte d'Ivoire and possible health implications - Yobouet, B.A.; Kouamé-Sina, S.M.; Dadie, A.; Makita, K.; Grace, Delia; Dje, K.M.; Bonfoh, Bassirou (Springer, 2014)
In Africa, milk and dairy products play an important role in human nutrition but could represent a risk to human health, due to poor hygiene throughout the production chain. This study aimed firstly to assess the contamination of raw milk produced in traditional dairy farms in Abidjan with Bacillus cereus from farm to retail and secondly to assess the associated health risk for consumers in informal markets using a participatory approach. In total, 320 samples including 150 milk samples were collected in 15 purposively selected traditional dairy farms from four sites of Abidjan and analysed according to EN ISO 7932:2004 with slight modification. In addition, a survey was conducted in the three informal markets with 188 individuals who bought milk. B. cereus was found in 27% of the udder milk samples while 41% of the samples taken from seller’s pooled milk contained B. cereus. Out of the 183 milk consumers, 14% reported daily consumption of unheated milk, indicating the high probability of exposure to B. cereus and other foodborne illnesses. After milk consumption, 13% of consumers reported that they contracted a foodborne illness. In conclusion, milk produced and sold in informal markets in Abidjan represents a risk for consumers’ health and B. cereus is one possible cause. Milk quality could be improved by good hygiene practices, strengthening and targeting educational interventions and effective monitoring throughout the production and delivery chain.